On Credibility and Causality in Economics: A Critical Appraisal - Andreas Bergh; Philipp C. Wichardt (CESifo GmbH, 2024)
Establishing causal relationships is a core aspect of empirical economics. Borrowing ideas from the medical sciences, we propose tentative guidelines for reliable causal inferences that cover aspects related to both the study itself and its fit with the existing background knowledge. We argue that the current paradigm in economics (often connected to the credibility revolution) tends to put too much emphasis on internal aspects related solely to the study itself. To illustrate and substantiate this view, we discuss various excellent studies from different fields of economics, which all express causal and highly policy relevant claims. From an applied point of view, the conclusion drawn is that policy implications based on single studies are inherently uncertain, even when the respective studies are state of the art.
Keywords: B41; C90; D90; 330; causality; empirical economics; methodology; credibility